2015
DOI: 10.1103/physreve.92.012817
|View full text |Cite
|
Sign up to set email alerts
|

Memory and burstiness in dynamic networks

Abstract: A discrete-time random process is described which can generate bursty sequences of events. A Bernoulli process, where the probability of an event occurring at time t is given by a fixed probability x, is modified to include a memory effect where the event probability is increased proportionally to the number of events which occurred within a given amount of time preceding t. For small values of x the inter-event time distribution follows a power-law with exponent −2−x. We consider a dynamic network where each … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…, N an activity a i drawn from a distribution ρ(a i ). The activation rate of node i is defined by its inter-event time distribution Ψ a i (τ ) [8][9][10][11][12]: this sets the statistic of time intervals between consecutive activations of node i, so that the average inter-event time equals the inverse of the activity of node i, i.e. τ i = a −1 i .…”
Section: Activity-driven Temporal Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…, N an activity a i drawn from a distribution ρ(a i ). The activation rate of node i is defined by its inter-event time distribution Ψ a i (τ ) [8][9][10][11][12]: this sets the statistic of time intervals between consecutive activations of node i, so that the average inter-event time equals the inverse of the activity of node i, i.e. τ i = a −1 i .…”
Section: Activity-driven Temporal Networkmentioning
confidence: 99%
“…Besides, a large amount of work has been devoted to clarify the effects of intermittent patterns on the temporal structures of interactions, as described by temporal networks [7]. Bursty dynamics can indeed influence the structure of links on the local and on the global scale [8][9][10][11][12]. More importantly, heterogenous temporal patterns in the evolution of time-varying networks can affect in a non-trivial way dynamical processes.…”
mentioning
confidence: 99%
“…However, recent works have showed that further detail analysis is required to resolve temporal correlations [31,32], bursts [19][20][21][22], and cascading [53] driven by circadian rhythm [23,24], complex decision-making of individuals [3,27,54], and external factors [6] such as the announcement of discoveries, as considered in the current data [38].…”
Section: Local Variationmentioning
confidence: 99%
“…The time series of user activities, e.g., posting a tweet and replying to a message, are quite distinct from uncorrelated (Poisson random) dynamics in the presence of burstiness [18][19][20], temporal correlations [6,21,22], and non-stationarity of human daily rhythm [23,24], which has significant implications. Diffusion on a temporal network cannot be accurately described by models on static networks and consequently the process presents non-Markovian features with strong influence on the time required to explore the system [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Several models of temporal networks have been put forward in the literature [22][23][24][25][26], focused on different possible mechanisms to explain the empirically observed properties. Among those, it is noteworthy the recently proposed Non-Poissoinan activity driven (NoPAD) model [27].…”
Section: Introductionmentioning
confidence: 99%